Reversible Disruption of Dynactin 1-Mediated Retrograde Axonal Transport in Polyglutamine-Induced Motor Neuron Degeneration - Katsuno, Masahisa (J Neurosci, 2006)
Spinal and bulbar muscular atrophy (SBMA) is a hereditary neurodegenerative disease caused by an expansion of a trinucleotide CAG repeat encoding the polyglutamine tract in the androgen receptor (AR) gene. To elucidate the pathogenesis of polyglutamine-mediated motor neuron dysfunction, we investigated histopathological and biological alterations in a transgenic mouse model of SBMA carrying human pathogenic AR. In affected mice, neurofilaments and synaptophysin accumulated at the distal motor axon. A similar intramuscular accumulation of neurofilament was detected in the skeletal muscle of SBMA patients. Fluoro-gold labeling and sciatic nerve ligation demonstrated an impaired retrograde axonal transport in the transgenic mice. The mRNA level of dynactin 1, an axon motor for retrograde transport, was significantly reduced in the SBMA mice resulting from pathogenic AR-induced transcriptional dysregulation. These pathological events were observed before the onset of neurological symptoms, but were reversed by castration, which prevents nuclear accumulation of pathogenic AR. Overexpression of dynactin 1 mitigated neuronal toxicity of the pathogenic AR in a cell culture model of SBMA. These observations indicate that polyglutamine-dependent transcriptional dysregulation of dynactin 1 plays a crucial role in the reversible neuronal dysfunction in the early stage of SBMA.